A Written Orality : The Canadian Inuitand Their Language - Dorais, Louis-Jacques (Kungl. Konsthögskolan, 2019)
This essay belongs to a set of materials published in reference to the transformative developments occurring in the realm of writing and speaking today, as triggered by digital communication. These shifts are part of a cultural process, shaped by structural multilingualism, which is impacting many parts of the globe. Fog Friend Font, the editorial framework for these collected and commissioned materials, was initiated by Hinrich Sachs and Fredrik Ehlin, and published by Humboldt Books, Milan.